ANALISIS KEIKUTSERTAAN BPJS â€œMANDIRIâ€ BERDASARKAN STATUS EKONOMI, SIKAP DAN PERSEPSI ATAS MUTU LAYANAN - ., Johariyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Today BPJS is one of hot issues that a lot of discussion not only by a group of health provider alone, but by most of the general public. Lack of socialization BPJS caused by the majority of people still do not have complete information, such as compliance with the terms and conditions of membership of BPJS â€œmandiriâ€. Purpose: To know the factors affecting the participation of BPJS â€œMandiriâ€. The method in this research is a comparative analysis with cross sectional approach, by comparing the obstetric patients who use BPJS â€œMandiriâ€ and patients with own payment. Sampling technique used is purposive sampling, with 30 people for each group. The data analysis is done by using SPSS. The data were analyzed two phases. The first stage is to analyze the economic status, attitudes and perceptions of quality of care in patients with BPJS â€œMandiriâ€ payment and own payment. The second stage is a comparative analysis of economic status, attitudes and satisfaction with services between patients by own payment and BPJS Mandiri payment. The results showed that the economic status in patient by BPJS Mandiri largely on the category low that as many as 73, 3 %, while attitudes toward BPJS mostly in the category of support that is equal to 86.7%. While the perception of the quality of most of the high category, 87%. In patients with own payments, based on the economic status, majority are high by 60%, majority by are support that is equal to 53.3%, and all responden (100%) have the perception of service quality in the high category. Based on the analysis we find that there is a significant relationship with an OR of 7.07 between economic status and participation of BPJS â€œMandiriâ€, signofikan relationship exists between attitudes toward BPJS with the participation of BPJS â€œMandiriâ€ with OR 6.48 and there was no correlation between perceptions of service with the participation BPJS Mandiri. Keywords: participation, BPJS Mandiri, economic status, attitudes, perception